2014
DOI: 10.1182/blood.v124.21.3500.3500
|View full text |Cite
|
Sign up to set email alerts
|

CC-122 Degrades the Lymphoid Transcription Factor Aiolos (IKZF3) By Modulating Cereblon and Shows Clinical Activity in a Phase Ib Study of Subjects with Relapsed or Refractory Non-Hodgkin’s Lymphoma and Multiple Myeloma

Abstract: Background: CC-122 is a novel non-phthalimide analog of the IMiDs® immunomodulatory drugs (lenalidomide and pomalidomide) and a first in class PPMTM (Pleiotropic Pathway Modifier) compound with multiple biological activities including potent anti-proliferative activity against B-lineage cells (10-fold greater than lenalidomide), anti-angiogenic activity (100-fold greater than lenalidomide) and immunomodulatory effects (10-fold greater than lenalidomide). The molecular target of CC-122 is cereblon (CRBN), a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Most of the TEAE were manageable with dose interruptions or reductions, or with the use of appropriate supportive care, and the safety profile of avadomide was considered acceptable. Overall, the safety results of this study were consistent with the known safety profile of avadomide from global studies 12,13,15,19,20 …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Most of the TEAE were manageable with dose interruptions or reductions, or with the use of appropriate supportive care, and the safety profile of avadomide was considered acceptable. Overall, the safety results of this study were consistent with the known safety profile of avadomide from global studies 12,13,15,19,20 …”
Section: Discussionsupporting
confidence: 85%
“…Ex vivo studies showed that avadomide significantly activated T cells, as measured by a dramatic increase in IL‐2 secretion upon stimulation 6,11 . Avadomide also decreased CD19 + B cells and expanded cytotoxic memory T cells in patients with NHL 12,13 . Furthermore, paired biopsies from DLBCL patients showed increased infiltration of T cells and macrophages upon treatment with avadomide 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current treatment options for patients with advanced solid and hematologic malignancies relapsed or refractory to standard therapies are limited. Avadomide's cell-autonomous effects, immune modulation, and antiangiogenic activity make it a potential therapeutic agent for hematologic and solid tumors (1,2,10,11). Herein, we report results from the first-in-human phase I dose-escalation study of avadomide in patients with advanced solid tumors, non-Hodgkin lymphoma (NHL), and multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other potential immunomodulatory mechanisms for its activity in (GCB)-DLBCL likely do exist and may impact the nonimmune environment in vivo , in patients as well [301]. CC-122 has already demonstrated clinical activity as single-agent in DLBCL [ 300 – 302 , 303 ]. CC-122 is currently in phase I trials in patients with newly diagnosed DLBCL or relapsed/refractory DLBCL, either as a single-agent (NCT01421524) [ 300 – 302 , 303 ] (Additional file 1 : Table S2) or in combination with the novel dual mTORC1/mTORC2 inhibitor CC-223 [ 304 ], the novel BTK inhibitor CC-293 [ 305 ] and/or rituximab (NCT02031419) as well as in combination with obinutuzumab, (NCT02417285) [ 303 ] (Additional file 1 : Tables S5 and S14).…”
Section: Introductionmentioning
confidence: 99%